Beginning ASP.NET MVC 1.0 - Chiaretta, Simone (Wrox beginning guides., 2009)
ASP.NET MVC (Model View Framework) allows you to use ready-to-use MVC code so you can develop Web applications faster. This book?s cut-to-the-chase approach gets you up to speed on the new ASP.NET MVC without getting bogging you down in learning or re-learning ASP.NET itself. You?ll receive straightforward instruction on concepts, backed by real-world case studies and examples that offer practical solutions. Topics include test-driven development and unit testing, the principles of the MVC pattern, how to implement it, how to move from traditional ASP.NET Webforms to ASP.NET MVC, and much more.